Review of Decadal Changes in ASEAN Emissions Based on Regional and Global Emission Inventory Datasets - Shimul Roy; Yun Fat Lam; Shauhrat S. Chopra; Md. Mahbubul Hoque (Aerosol and Air Quality Research)
Abstract In Asia, anthropogenic emissions have increased substantially over the last decade from various sectors, including power generation (PG), industries, road transportation (RT), and residential. This study analyzed different regional (REAS, MIX-Asia) and global (EDGAR) emission inventory (EI) datasets to provide insight into ASEAN’s comprehensive emission status (emission trend, sectoral and country-specific emissions, changes in spatial distribution) during 2000–2015. The study observed a considerable increase in SO2, NOx, CO, CO2, and particulate matter (PM) emissions in ASEAN during this period. Results analyzed from the EDGAR EI dataset (2015) show that among the pollutants, SO2, CO2, and N2O were substantially contributed by the PG sector (43.4–56%), while CO, NOx, NMVOC, and CH4 were from the RT sector (35.6–61.5%), and PM and NH3 emissions were from the residential sector (50–80.6%). Similar contributions were also observed in 2000 and 2010. It is apparent that these sectors contributed noticeably to the total Asian emission (i.e., 14–34% in 2010, based on the MIX-Asian dataset). We have observed increasing annual emission trends for most pollutants in ASEAN countries, with more significant emission growth in Vietnam (e.g., SO2 and NOx emissions increased by 232% and 145%, respectively). Considerable changes in spatial emission distributions over the ASEAN between that period were also observed caused by the shifting of sparse development into concentrated urban expansion surrounding large metropolitan clusters. The information from this study will be vital for the ASEAN governments to review and update their approved/planned regulations on emission control with prioritizing the sectors aimed at air quality management and environmental sustainability.